REVITALISASI EKS BANDARA KEMAYORAN - Alvin Rivaldo Ngaginta; James Erich D. Rilatupa (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Urban acupuncture is a method applied to revive a particular area through local internventions; This intervention is believed to act as a catalyst which could bring a previously dead or damaged back to life. Kemayoran International Airport was the first international airport in Indonesia, which operated from 1940 to 1985, when the Soekarno Hatta airport was opened. Now all that is left is an abandoned building, which holds a historical value with the potential of re-development and should be preserved accordingly. Despite being located in quite a crowded area, the condition of the building creates an unappealing atmosphere to its surroundings. Therefore, this project aims to revive the building previously known as Kemayoran airport, to fulfill the potential that it holds, by using the adaptive reuse method which is supported by architectural technologies for realization, in hopes that this would result in the increase of crowd numbers, therefore supporting the economic conditions of nearby areas. The main program included in this building was an aviation museum which tells the history of Kemayoran airport at its glory; Moreover, this building also includes a co-working space and a community center, as a respond to the vision of PPPK which is to make the area into a business district. With this revitalization, it is hoped that the former Kemayoran Airport can function again and have a positive impact on its surroundings. Keywords: Adaptive Reuse; Architectural Technology; Aviation Museum; Kemayoran Airport; Revitalization; Urban Acupuncture Abstrak Urban acupuncture merupakan metode yang diaplikasikan untuk menghidupkan kembali suatu kawasan melalui intervensi lokal; Intervensi ini diharapkan untuk berfungsi sebagai katalistor yang dapat menghidupkan kembali kawasan yang sudah mati atau rusak. Bandar Udara Internasional Kemayoran merupakan bandara internasional pertama di Indonesia, yang resmi beroperasi dari tahun 1940 sampai 1985, pada saat bandara Soekarno-Hatta dibuka. Kini, yang tersisa hanyalah bangunan terbengkalai, sedangkan bangunan tersebut sebenarnya memiliki nilai historis yang seharusnya dipelihara selayaknya dan berpotensi untuk dikembangkan kembali. Walaupun berada di kawasan yang cukup ramai dengan pengunjung, tetapi kondisi bangunan tersebut membuat suasana sekitar menjadi kurang mengenakan. Maka dari itu, proyek ini bertujuan untuk menghidupkan kembali bangunan eks Bandara Internasional Kemayoran sesuai dengan potensi yang dimilikinya, dengan menggunakan metode adaptive reuse yang didukung dengan teknologi arsitektur untuk merealisasikannya, dengan harapan bahwa hasil dari revitalisasi ini akan meningkatkan jumlah pengunjung yang akan membantu perekonomian kawasan sekitar. Program utama yang terdapat dari bangunan ini merupakan museum aviasi yang menceritakan sejarah bandara Kemayoran pada masa kejayaannya; Selain dari itu, pada bangunan ini juga terdapat co-working space dan community center, sebagai respon dari visi PPPK yang akan menjadikan kawasan tersebut sebagai kawasan bisnis. Dengan adanya revitalisasi ini diharapkan Eks Bandara Kemayoran dapat berfungsi kembali dan membawa dampak positif terhadap sekitarnya.